New Application of the Commercially Available Dye Celestine Blue B as a Sensitive and Selective Fluorescent "Turn-On" Probe for Endogenous Detection of HOCl and Reactive Halogenated Species - Veronika E. Reut; Stanislav O. Kozlov; Igor V. Kudryavtsev; Natalya A. Grudinina; Valeria A. Kostevich; Nikolay P. Gorbunov; Daria V. Grigorieva; Julia A. Kalvinkovskaya; Sergey B. Bushuk; Elena Yu Varfolomeeva; Natalia D. Fedorova; Irina V. Gorudko; et al. (MDPI AG, 2022)
Hypochlorous acid (HOCl) derived from hydrogen peroxide and chloride anion by myeloperoxidase (MPO) plays a significant role in physiological and pathological processes. Herein we report a phenoxazine-based fluorescent probe Celestine Blue B (CB) that is applicable for HOCl detection in living cells and for assaying the chlorinating activity of MPO. A remarkable selectivity and sensitivity (limit of detection is 32 nM), along with a rapid "turn-on" response of CB to HOCl was demonstrated. Furthermore, the probe was able to detect endogenous HOCl and reactive halogenated species by fluorescence spectroscopy, confocal microscopy, and flow cytometry techniques. Hence, CB is a promising tool for investigating the role of HOCl in health and disease and for screening the drugs capable of regulating MPO activity.